"Fear of Flying": competing notions of flying disorders in World War II and the Korean War - Pitt, Jorden David (Kansas State University, 2019)
During World War II and the Korean War, military medical officers diagnosed many pilots with a psychological disorder known as “Fear of Flying,” (FOF) which is very similar to today’s Post Traumatic Stress Disorder. There were two competing paradigms regarding this problem and whether it was truly a sickness. Medical personnel such as psychologists defined Fear of Flying as a mental illness thereby establishing a “Mental-Illness” hypothesis. Administrative Personnel, such as commanding officers and other ranked officials, subscribed to the notion that the disorder was not a true sickness. They believed that the men who confessed that they suffered from FOF evinced cowardice. Therefore, officers created the “Character-Flaw” paradigm. These two schools of thought, therefore, dictated the way psychologists and officers diagnosed, evaluated, and cured or inoculated/quarantined Fear of Flying in the Second World War and the Korean War. Examining these different stages—diagnosis, evaluation, and cure/prevention—allow one to gain a better understanding of how medical professionals and commanding officials perceived psychological illnesses in the 1940s and 1950s. Flying disorders that some World War II and Korean War pilots experienced also reveal the competing notions between the two different military factions regarding mental disorders in times of war, thereby granting scholars new analytical lenses through which they can view inner-conflict in the military and issues of masculinity in the 1940s and 1950s.
Keywords: Fear of Flying; Flight Disorders; Lack of Moral Fiber; World War II; Korean War; Masculinity